Whole-genome sequencing, annotation, and biological characterization of a novel Siphoviridae phage against multi-drug resistant Propionibacterium acne - Liao, Danxi; Zhang, Jian; Liu, Ruolan; Chen, Kui; Liu, Yuanyuan; Shao, Yuming; Shi, Xi; Zhang, Yiming; Yang, Zichen (Frontiers in Microbiology, 2023)
Antibiotics-resistant Propionibacterium acne (P. acne) causes severe acne vulgaris, serious public health and psychological threat. A new lytic bacteriophage (phage), φPaP11-13, infecting P. acne, was isolated from the sewage management center of Xinqiao Hospital. It can form transparent plaque with diameters of 1.0 ~ 5.0 mm on the double-layer agar plate, indicating a robust lytic ability against its host. Transmission electron microscopy (TEM) showed that φPaP11-13 belonged to the Siphoviridae family (head diameter 60 ± 4.5 nm, tail length 170 ± 6.4 nm, tail width 14 ± 2.4 nm). The one-step growth curve showed the incubation period was 5 hours and the burst size was 26 PFU (plaque forming unit)/cell. Moreover, it exhibited tolerance over a broad range of pH and temperature ranges but was utterly inactivated by ultraviolet (UV) irradiation for one hour. The whole-genome sequencing results revealed φPaP11-13 had a linear dsDNA with 29,648 bp length. The G/C content was 54.08%. Non-coding RNA genes and virulence factors were not found. 45 open reading frames (ORFs) were identified after online annotation. This study reports a novel P. acne phage φPaP11-13, which has a robust lytic ability, no virulence factors, and good stability. The characterization and genomic analysis of φPaP11-13 will develop our understanding of phage biology and diversity and provide a potential arsenal for controlling antibiotics-resistant P. acne-induced severe acne vulgaris.